Immigration as a peril - Stingley, John (My University, 1894)
Introduction: What is the most noticeable feature of our time? It is the steady influx of emigrants into one country and this will probably continue as long as we continue to offer such inducements as we have been, in the form of cheap land, ample protection under our government, and prospective business without requiring scarcely anything for one privileges of citizenship. No one is surprised in the least when a poor unfortunate man leaves his nature country and seeks peace under the protection of the governments of the west, where pleas and homes may be had upon farms which the gov. simply gives away.
Citation: Stingley, John. Immigration as a peril. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Immigration; Peril; Farm; Government; Land; Political science; Anthropology; Theses; Manuscripts (documents)